An exploratory study of pupils’ experiences of Pupil Referral Units and the perceived impact on self-identity - Sangha, Kieranjit (2019)
The purpose of this research was to explore students’ experiences of Pupil Referral Units and the perceived impact of their experiences on their self-identity. The aim of the research was to contribute to the existing evidence base regarding the impact of exclusionary practices for young people. The researcher sought to increase awareness of the unique perspectives of young people, in order to increase understanding of what young people might be experiencing during the event of informal or formal exclusion. Semi-structured interviews were conducted with five students aged 13 and 14. All students were placed in a local Pupil Referral Unit (PRU). The researcher used thematic analysis using guidance by Smith, Flowers and Larkin (2009) as a methodological approach to analysing data collected through interviews. Eight Master Themes were derived from the interpretative analysis. Pupils expressed uncertainty about the setting upon entry following an experience of ‘failure at mainstream’. They experienced ‘positive and provocative relationships at the PRU’ with both adults and peers. A shared experienced by students at the PRU related to perceived ‘unfair behavior management’ and their tendency to make a ‘comparison with mainstream’ experiences. Finally, their experience at the PRU was affected by ‘a lack of knowledge, stability, involvement and certainty about their personal situation’ and placement at the PRU. With regard to self-identity, the participants often held ‘perceptions of themselves as aggressive and naughty’. They held ‘concerns that others viewed them negatively’, based on attributions made about them by education professionals and the related stigma of being placed in a PRU. Finally, participants had ‘concerns about the potential damaging impact on their future career opportunities and aspirations’ of being placed in a PRU. The research findings are discussed in relation to existing literature. Wider implications include the implementation of an induction process for new PRU pupils, redesigning referral systems into the PRU to prevent pupils remaining there for an extended period, as well as reviewing behaviour management policies to include restorative practices, and building students’ capacity to regulate their emotions in a safe way. Implications for Educational Psychologists include obtaining the voice of the child and providing clear information to pupils about statutory processes, alongside close working with PRUs to prevent exclusion.